Створення генетичних джерел селекційно-цінних ліній запилювачів на основі діалельних гібридів цукрових буряків - Корнєєва, М.О.; Ненька, О.В. (Фактори експериментальної еволюції організмів, 2016)
Aim. The first step towards the creation of donors is to identify and create sources of genetic selection of features. The
aim of the research was to determine genetic value of multigerm pollinators of sugar beet and create genetic sources of
high yield and sugar content signs. Methods. Selection of genetic sources of productivity was carried amongst interline
hybrids derived from diallel crosses (n2
combinations). Results. The article presents results on the selection of sources of
high productivity among interline hybrids of sugar beet, which components were evaluated by diallel scheme. It discusses
the genetic determination of agronomic traits taking into consideration additive gene actions in female component as
well as significant effect of inadditive interactions between components of hybridization. Revealed is the positive effect
of cytoplasm in phenotypic yield manifestations, on sugar content and sugar yield in direct hybrids in reciprocal crosses.
Conclusions. Based on the obtained results, samples BZ1/BZ2 and BZ1/BZ4 combining both high yield and sugar content
among diallel hybrids were selected, which can serve as sources of genes of high productivity. Female component of the
hybrid combinations (line BZ1) was notable for high general combining ability for yield, and lines BZ2 and BZ4 for sugar
content and sugar yield, respectively.
Keywords: sugar beet, pollinators, combination ability, heterosis, diallel hybrids.